Translation and validation of the Comfort Behaviors Checklist in hospitalized children with chronic diseases - Sara Valadkhani; Sima Hejazi; Azam Shirinabadi Farahani (BMC, 2023)
Abstract Background Different tools have been developed to measure patients' comfort. This study aims to translate, validate, and apply the Comfort Behaviors Checklist to hospitalized children with chronic diseases. Methods Validity and reliability are assessed using face and content validity, construct validity (known-groups technique and Principal Component Analysis), internal consistency, and inter-rater reliability. The study takes place in a children's hospital in Iran, involving 220 children aged 4 to 6. Results The Comfort Behaviors Checklist demonstrates acceptable face and content validity. Construct validity is supported by the lack of correlation between behavioral comfort scores in known groups. The Principal Component analysis results in five components, explaining 70.39% of the total variation. The checklist exhibits acceptable reliability, with a total Cronbach's alpha coefficient of 0.86 and an intraclass correlation coefficient of 0.835. Conclusion The Comfort Behavior Checklist is a valid and reliable tool for assessing the level of comfort in Iranian children with chronic diseases.